704 Laparoscopic Cholecystectomy for Ultrasound Proven Gallbladder Polyps – an Unsound Indication?. (19th August 2022) - Bezzaa, S; Clements, C; Patel, P; Kumapley, L; Burney, K; Nehra, D
Abstract: Aim: Current European guidelines recommend cholecystectomy for ultrasound proven gallbladder polyps based on size. Over-diagnosis of gallbladder polyps by conventional transabdominal ultrasound may lead to unnecessary surgery. The aim of this study is to correlate the ultrasound findings of gallbladder 'polyps' with histology of the removed gallbladder specimens. Method: Data from transabdominal ultrasound reports was collected over a 5-year period and cross-referenced with the histology from patients undergoing a laparoscopic cholecystectomy over the same time-period. Results: 60 patients who underwent laparoscopic cholecystectomy with ultrasound proven gallbladder polyps were identified. The age range was 19–79 years. There were 36 females and 24 males. On imaging 30 patients (50%) had a solitary polyp (size range 2–24mm) and 30 (50%) had multiple polyps (largest polyp size range 4–13mm). The indication for cholecystectomy was gallbladder polyps with or without gallstone disease in 32 patients (53%) and gallbladder or gallstone disease with incidental polyps in 28 patients (47%). Only 2/60 (3.3%) patients had adenomatous polyps on histology (9mm and 9.7mm on ultrasound), whilst 18/60 (30%) had pseudopolyps and in the remaining 40 specimens, no lesion of polypoidal type was found. No specimens had evidence of dysplasia or malignancy. Conclusion: We propose that an ultrasound abdomen is an inadequate imaging modality alone to diagnose gallbladder polyps and that patients require further imaging or MDT discussion as adjuncts to decision making for those referred for consideration of cholecystectomy.